Reading skills in hyperlexia: a developmental perspective. - Nation, K (1999)
Hyperlexia is characterized by advanced word-recognition skills in individuals who otherwise have pronounced cognitive, social, and linguistic handicaps. Language, word recognition, and reading-comprehension skills are reviewed to clarify the nature and core deficits associated with the disorder. It is concluded that hyperlexia should be viewed as part of the normal variation in reading skills, which are themselves associated with individual differences in phonological, orthographic, and semantic processing, short-term memory, and print exposure. A compulsive preoccupation with reading may also be crucial to the development of a hyperlexic reading profile. A theoretical framework, based on recent connectionist models of reading development, is described. This perspective provides a satisfactory account for how individual differences in a number of different skills can lead to a variety of manifestations of reading behavior, including hyperlexia.